Being intimate with flies: on affective methodologies and laboratory work - Mehrabi Tara (My University, 2022)
Situated within feminist technoscience studies and affect theory, this article explores the methodological specificities of working with Drosophila Melanogaster, commonly known as fruit flies. Based on a year of participatory observation in a fly lab, the article challenges the modernist imaginaries of laboratory work as disembodied, detached and objective. It suggests that laboratory work is instead an interactive, embodied and affective process that takes place in proximity between human and non-human, subject and object. The article therefore contributes to earlier feminist science studies arguing that doing science is an interactive, procedural, socio-cultural phenomenon. However, while most such previous works focus on issues such as connections, companionship, love and empathy, this article asks what  ethodological contributions can come from experiencing the intensity of more than human encounters that inspire undesirable feelings such as disgust.